POTENSI KONSORSIUM Bacillus spp. DAN Pseudomonas fluorescens UNTUK MENGENDALIKAN PENYAKIT LAYU FUSARIUM PADA TANAMAN CABAI RAWIT - Nensi Agustina; Arika Purnawati; Endang Triwahyu Prasetyawati (UPN VETERAN JAWA TIMUR, 2022)
Cayenne pepper (Capsicum frutescens L.) is one of the horticultural crops with high economic value. The production of cayenne pepper is often constrained by stem wilt disease caused by the fungus Fusarium sp. This research aims to know the effect of the consortium of Bacillus spp. and Pseudomonas fluorescens as biological agents to control fusarium wilt in cayenne pepper. This research was conducted at the screenhouse of UPN